Characterisation of phenolic compounds of the ethyl acetate fraction from Tabernaemontana catharinensis and its potential antidepressant-like effect. Issue 16 (18th August 2018) - Pauleti, Nathielli Nayara; Mello, Jonas; Siebert, Diogo Alexandre; Micke, Gustavo Amadeu; de Albuquerque, Cláudia Almeida Coelho; Alberton, Michele Debiasi; Barauna, Sara Cristiane
Abstract: This study evaluates the antidepressant-like effect and analysed the qualitative and quantitative 74 phenolic standards of ethyl acetate fraction from Tabernaemontana catharinensis leaves. Acute administration of fraction in mice reduced the immobility time in forced swimming and tail suspension tests confirming its antidepressant-like activity. The anti-immobility effect elicited by this fraction was prevented by the pretreatment of mice with PCPA (100 mg kg −1 ), ketanserin (5 mg kg −1 ), SCH 23, 390 (0.05 mg kg −1 ) or yohimbine (1 mg kg −1 ). A sub effective dose of the fraction produced a synergistic effect with fluoxetine (5 mg kg −1 ). Chromatographic analysis identified 4-hydroxybenzoic and p -coumaric acids in the ethyl acetate fraction from T. catharinensis . Capillary electrophoresis presented 7.34 ± 0.02 mg g −1 of p -coumaric acid concentration in the fraction. Therefore, it is possible that antidepressant-like effect elicited by ethyl acetate fraction from T. catharinensis be dependent on the p -coumaric acid. Abstract :